Canine oral eosinophilic granuloma treated with corticosteroid monotherapy - case report - J.D. Rocha Júnior; G.G. Cabral; L.F. Mangolin; D.C. Sousa; C.C.F. Mazula; T. Santos; B.H. Malfacini; M.B. Almeida; P.R.R. Moreira; F.G. Gonçalves Dias (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Eosinophilic granuloma is a lesion commonly found in cats but is rare in dogs, manifesting as nodules or plaques in the oral cavity, especially on the soft palate and tongue, with possible genetic potential involved. Due to the scarcity of descriptions of this oral lesion in dogs, especially in Brazil, the present report aimed to describe it in a Siberian Husky, treated at the Veterinary Hospital of the University of Franca, presenting an adherent and ulcerated plaque on the soft palate. Histopathological examination detected intense eosinophilic infiltrate associated with areas of collagenolysis, absence of neoplastic cells and negative PAS staining. Corticosteroid therapy with prednisolone (2mg/kg, every 24 hours, 7 days) was instituted, with gradual weaning of 0.5mg/kg, every 7 days. Given the excellent therapeutic response, this medication was maintained as monotherapy and, within 90 days of the end of treatment, there were no signs of relapse, without the need for association with complementary therapies or other therapeutic modalities, which could cause adverse effects and additional costs. It is admitted that, despite being uncommon, due to its similar clinical appearance, eosinophilic granuloma should be included in the differential diagnosis of neoplasms and infections, aiming at appropriate therapeutic institution.